Interactions between Convection and a Moist Vortex Associated with an Extreme Rainfall Event over Southern West Africa - AKPO, ARISTIDE BARTHÉLÉMY; MARANAN, Marlon (My University, 2019)
An intense mesoscale convective system (MCS) in the Guinea Coast region caused one of the highest ever recorded daily rainfall amounts at the Nigerian station Abakaliki on 12 June 2016 (223.5mm). This paper providesadetailedanalysisofthemeso-andsynoptic-scale factorsleadingtothisevent,includingsomeso far undocumenteddynamicalaspectsforsouthernWestAfrica.TheMCSformedovertheDarfurMountainsdue to diurnal heating, then moved southwestward along a mid- to lower-tropospheric trough, and developed into a classical West African squall line in a highly sheared environment with pronounced midlevel dryness. Strong moistureﬂuxconvergence overNigeriaprior to the MCS passageled toextremevaluesinprecipitable water and was caused by the formation of a local, short-lived heat low. According to the pressure tendency equation, the latter resulted from tropospheric warming due to MCS-forced subsidence as well as surface insolation in the resulting almost cloud-free atmosphere. In this extremely moist environment, the MCS strongly intensiﬁed and initiated the formation of a lower-tropospheric vortex, which resulted in a de- celeration of the MCS and high rainfall accumulation at Abakaliki. Following the vorticity equation, the vortex formation was realized through strong low-level vortex stretching and upper-level vertical vorticity advection related to the MCS, which became ‘‘dynamically large’’ compared to the Rossby radius of de- formation. Eventually, moisture supply and lifting associated with the vortex are suggested to promote the longevity of the MCS during the subsequent westward movement along the Guinea Coast.